Full-solid secondary battery

The all-solid-state secondary battery design with a lower modulus back layer in the current collector addresses short circuit issues by enabling deformation without breaking, ensuring stable operation and easy assembly.

JP2025010702APending Publication Date: 2025-01-23GS YUASA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023112835
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

All-solid-state secondary batteries with active material layers containing metals or alloys that can absorb or release alkali metal ions face issues with short circuits during charging and discharging.

Method used

The battery design includes a pair of electrodes with a solid electrolyte layer in between, where at least one electrode is made of a metal that can occlude or release alkali metal ions, and a current collector with a metal layer and a back layer having a lower Young's modulus, which allows for deformation without breaking, thus preventing short circuits.

Benefits of technology

The design effectively suppresses short circuits during charging and discharging while maintaining high energy density by allowing the current collector to deform without breaking, facilitating easy assembly and reducing the risk of cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010702000001_ABST
    Figure 2025010702000001_ABST
Patent Text Reader

Abstract

To provide a full-solid secondary battery capable of suppressing a short-circuit at a charging and a discharging, while having an activation layer containing a metal or their alloy which can occlude or discharge an alkali metal ion.SOLUTION: A full-solid secondary battery 10 according to one side surface of the present invention, comprises active material layers 5 and 6 in which a pair of electrodes are faced via a solid electrolyte layer 3, at least one of the pair of electrodes 1 and 2 contains a metal and their alloy that absorbs or discharges an alkali metal ion. At least one of the pair of electrodes comprises: a metal layer 4a provided to each active material layer side; and a collector 4 that is provided to the side opposite to the active material layer 5 against the metal layer 4a, and contains a back surface layer 4b of which a Young ratio is smaller than that of the metal layer 4a.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state secondary battery. [Background technology]

[0002] In recent years, the development of all-solid-state secondary batteries that use flame-retardant solids as electrolytes has been progressing. As an all-solid-state secondary battery, a battery in which a polymer material is arranged on the electrodes is known.

[0003] Patent Document 1 describes, as Example 1, "Cu foil... was prepared as the current collecting portion of the negative electrode current collector, and silicone rubber... having electronic conductivity was prepared as the elastic portion of the negative electrode current collector. In addition, a sulfide solid electrolyte (a Li2S-P2S5-based material containing LiBr and LiI) was prepared as a solid electrolyte for forming a solid electrolyte layer. Furthermore, Li foil was prepared as a positive electrode (counter electrode). Thereafter, the sulfide solid electrolyte... was press-molded to form a solid electrolyte layer. Li foil was placed on one side of the obtained solid electrolyte layer, and Cu foil and rubber were placed on the other side, and the resulting solid electrolyte layer was press-molded to form a power generating element.... The resulting power generating element was restrained... to obtain a battery for evaluation. The resulting battery for evaluation has a layered structure in which SUS, Li foil, solid electrolyte layer, Cu foil, rubber, and SUS are arranged in this order, as shown in FIG. 5(a)." (Paragraphs

[0067] to

[0068] )

[0004] Patent Document 2 states, "Three monopolar battery units were fabricated in which a positive electrode collector layer, a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, a negative electrode collector layer, a negative electrode active material layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode collector layer were laminated in this order. These monopolar battery units were stacked on top of each other with an insulating polymer film sandwiched between them. The positive electrode current collector layers and negative electrode current collector layers of each stacked monopolar battery unit were connected as shown in FIG. 2 to complete the all-solid-state battery stack of Example 1." (Paragraphs

[0093] to

[0094] )

[0005] Patent Document 3 states, "Using the following materials, a battery stack 10 having a stacked structure as shown in FIG. 1 was prepared, and its sides were covered with a resin layer 11 and restrained with a restraining force of 10 MPa to prepare all-solid-state batteries of Examples 1 to 3 and Comparative Examples 1 and 2. ·Positive electrode current collector layer: Aluminum current collector foil· · Positive electrode active material layer: Positive electrode active material + sulfide solid electrolyte + conductive additive + binder... Cathode active material: LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2 Sulfide solid electrolyte: Li2S-P2S5-LiI-LiBr Conductive additive: Vapor grown carbon fiber (VGCF) Binder: Polyvinylidene fluoride (PVdF) ·Solid electrolyte layer: Sulfide solid electrolyte + binder· Sulfide solid electrolyte: Li2S-P2S5-LiI-LiBr Binder: Styrene butadiene rubber (SBR) Negative electrode active material layer: Si alloy-based negative electrode active material + sulfide solid electrolyte + binder Sulfide solid electrolyte: Li2S-P2S5-LiI-LiBr Binder: Polyvinylidene fluoride (PVdF) ·Positive / negative electrode current collector layer: SUS current collector foil· As the resin material constituting the resin layer, silicone resin was used in Examples 1 to 3, and epoxy resin was used in Comparative Examples 1 and 2. Filler was added appropriately to adjust the relationship with the compressive elastic modulus of the battery laminate." (Paragraphs

[0084] to

[0086] )

[0006] Patent Document 4 states, "(Preparation of Positive Electrode Structure) LiNi as a positive electrode active material 0.8 Co 0.15 Al 0.05O2(NCA) ternary powder, Li2S-P2S5... amorphous powder as a sulfide-based solid electrolyte, and vapor-grown carbon fiber powder as a positive electrode layer conductive material (conductive additive)... were weighed and mixed using a planetary centrifugal mixer. Next, a dehydrated xylene solution in which styrene-butadiene rubber (SBR) was dissolved as a binder was added to this mixed powder to prepare a primary mixed liquid. Furthermore, an appropriate amount of dehydrated xylene was added to this primary mixed liquid to prepare a secondary mixed liquid. Furthermore, zirconia balls with a diameter of 5 mm were placed into the secondary mixed liquid. The tertiary mixed liquid thus produced was placed in a planetary centrifugal mixer and stirred to prepare a coating liquid for the positive electrode active material layer. Next, an aluminum foil current collector was prepared as a positive electrode current collector, the positive electrode active material layer coating liquid was applied onto the aluminum foil current collector, and then the aluminum foil current collector coated with the positive electrode active material layer coating liquid was dried on a hot plate. Next, the positive electrode active material layer coating liquid was also applied to the back side of the aluminum foil current collector, and then dried on a hot plate. Next, the coated aluminum foil current collector was further vacuum dried. As a result, positive electrode active material layers were formed on both sides of the positive electrode current collector, and a positive electrode structure was obtained. (Preparation of negative electrode structure) A nickel foil current collector was prepared as the negative electrode current collector, and CB1 (amorphous carbon...) manufactured by Asahi Carbon Co., Ltd., CB2 (amorphous carbon...) manufactured by Asahi Carbon Co., Ltd., and silver particles were prepared as the negative electrode active materials. Next, CB1, CB2, and silver particles were placed in a container, and an N-methylpyrrolidone (NMP) solution containing a binder was added to obtain a mixed solution. Next, this mixed solution was stirred while adding NMP little by little to produce a slurry. This slurry was applied to a nickel foil current collector using a blade coater and dried in air. The laminate thus obtained was vacuum dried. Through the above steps, a negative electrode structure was produced in which a negative electrode active material layer was laminated on a negative electrode current collector. (Preparation of solid electrolyte negative electrode composite) Li2S-P2S5 as a sulfide-based solid electrolyte... A primary mixed slurry was produced by adding SBR binder dissolved in dehydrated xylene to amorphous powder... An appropriate amount of dehydrated xylene and dehydrated diethylbenzene was then added to this primary mixed slurry to produce a secondary mixed slurry. Furthermore,... zirconia balls with a diameter of 5 mm... were added to the tertiary mixed slurry. The tertiary mixed liquid produced in this way was then placed in a planetary centrifugal mixer... and stirred to produce an electrolyte layer coating slurry. The solid electrolyte slurry was applied onto the negative electrode structure. It was then dried on a hot plate and then vacuum dried to form a solid electrolyte layer. As a result, a solid electrolyte negative electrode composite was obtained in which a solid electrolyte layer was formed on the negative electrode structure. (Production of all-solid-state secondary batteries) After punching out the sheet-shaped solid electrolyte negative electrode composite and the sheet-shaped positive electrode structure with the positive electrode active material layer formed on both sides with a Thomson blade, the solid electrolyte negative electrode composite, the positive electrode structure, and the solid electrolyte negative electrode structure were stacked in this order so that the solid electrolyte layers were in contact with both sides of the positive electrode structure. In this state, they were placed in an aluminum laminate film, and the laminate was packed by evacuating with a vacuum machine. Next, it was placed on an aluminum plate (support plate) and vacuum laminated and packed, including the support plate. This was then submerged in a pressurized medium and subjected to isostatic pressure treatment (consolidation process). In this way, an all-solid-state secondary battery was produced as a single cell. In this case, the negative electrode current collector foil of the solid electrolyte negative electrode composite on the side in contact with the aluminum plate is called side A, and the negative electrode current collector foil on the opposite side is called side B. ... (Fabrication of stacked all-solid-state secondary batteries) The two single cells of the prepared all-solid-state secondary battery were insulated from each other, and the A side of one all-solid-state secondary battery was stacked with the B side of the other all-solid-state secondary battery facing each other, placed in an aluminum laminate film with terminals attached, evacuated with a vacuum machine, and then heat-sealed and packed to prepare a laminated all-solid-state secondary battery according to Example 1. (Paragraphs

[0111] to

[0121] ) The cited document 4 also states that the insulating layer is not particularly limited as long as it can insulate adjacent all-solid-state secondary batteries 1 from each other, and may be, for example, a thermoplastic resin sheet such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyurethane, polytetrafluoroethylene, or acrylic resin, a thermosetting resin sheet such as phenolic resin, epoxy resin, melamine resin, or urethane resin, an engineering plastic such as polyethylene terephthalate, polyamide, or polycarbonate, a synthetic rubber sheet such as silicone rubber or urethane rubber, or a sheet such as paper, or a resin coated on the all-solid-state battery 1. (Paragraph

[0081] )

[0007] Patent Document 5 states, "[Preparation of current collector for all-solid-state battery] Example 1 Acid-modified PVDF-A, acetylene black, poly(N-vinylpyrrolidone)-A, and titanium oxide particles were prepared, to which N-methyl-2-pyrrolidone and isopropyl alcohol were added. The mixture was mixed using a stirrer to obtain a coating solution. Next, an aluminum foil was prepared, the prepared coating liquid was placed in the liquid reservoir (pan) of the gravure coater, and the gravure roll was rotated at a constant speed. The aluminum foil was brought into contact with the gravure roll, and the aluminum foil was transported in the same direction as the gravure roll's rotation to coat it, and the applied coating liquid was then dried. The opposite side of the aluminum foil was coated with the coating liquid in the same manner and dried. (Paragraphs

[0101] to

[0103] ) LiCoO2... as a positive electrode active material, conductive carbon black... as a conductive assistant, polyvinylidene fluoride... as a binder, and LLTO (La2O3:Li2CO3:TiO2 molar ratio of 14:28:50)... as an oxide-based solid electrolyte were stirred and mixed while adding N-methyl-2-pyrrolidone appropriately to prepare a slurry-like dispersion. The prepared dispersion was applied to the current collectors prepared in Examples 1 to 3 and Comparative Example 1... using a doctor blade, dried, and pressure-molded to obtain an all-solid-state battery positive electrode sample. (Paragraph

[0109] ) and the description "[Evaluation of all-solid-state batteries] <Preparation of oxide-based solid electrolyte layer> The La2O3:Li2CO3:TiO2 molar ratio was weighed out to be 14:28:50 and mixed in a mortar. A small amount of ethanol was added to the mixture and wet-mixed in the mortar to obtain a slurry. The slurry was packed into a container with a diameter of 10 mm and uniaxially pressed to form pellets. The obtained pellets were pre-fired and then fired. <Production of all-solid-state batteries> The all-solid-state battery positive electrode sample was punched out to a diameter of 10 mm, and the oxide-based solid electrolyte layer pellet and Li metal foil punched out to a diameter of 10 mm were layered and pressed together in that order, and an aluminum laminate was used as the exterior material to fabricate an all-solid-state battery half cell." (Paragraphs

[0111] to

[0112] ) [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent Publication No. 2021-2495 [Patent Document 2] JP 2020-136261 A [Patent Document 3] JP 2020-21551 A [Patent Document 4] JP 2019-121558 A [Patent Document 5] Patent Publication No. 2021-99934 Summary of the Invention [Problem to be solved by the invention]

[0009] All-solid-state secondary batteries having an active material layer containing a metal or an alloy thereof capable of occluding or releasing alkali metal ions have had a problem of short circuit occurrence during charging and discharging.

[0010] Therefore, an object of the present invention is to provide an all-solid-state secondary battery that is provided with an active material layer containing a metal or an alloy thereof capable of occluding or releasing alkali metal ions and that is suppressed from short-circuiting during charging and discharging. [Means for solving the problem]

[0011] An all-solid-state secondary battery according to one aspect of the present invention includes a pair of electrodes opposed to each other via a solid electrolyte layer, at least one of the pair of electrodes having an active material layer containing a metal or an alloy thereof capable of absorbing or releasing alkali metal ions, and at least one of the pair of electrodes having a current collector including a metal layer provided on the active material layer side, and a backside layer having a Young's modulus smaller than that of the metal layer, the backside layer being provided on the opposite side of the metal layer from the active material layer. Effect of the Invention

[0012] An all-solid-state secondary battery according to one aspect of the present invention has an active material layer containing a metal or an alloy thereof capable of occluding or releasing alkali metal ions, and is suppressed from short-circuiting during charging and discharging. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a stacked-type all-solid-state secondary battery. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device configured by assembling a plurality of all-solid-state secondary batteries. [Diagram 3] FIG. 3 is a cross-sectional view showing the structure of an electrode body in the all-solid-state secondary battery produced in Example 1. [Figure 4] FIG. 4 is a cross-sectional view showing the structure of an electrode body in the all-solid-state secondary battery produced in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (1) An all-solid-state secondary battery according to one embodiment of the present invention has a pair of electrodes opposed to each other via a solid electrolyte layer, at least one of the pair of electrodes having an active material layer containing a metal or an alloy thereof capable of absorbing or releasing alkali metal ions, and at least one of the pair of electrodes having a current collector including a metal layer provided on the active material layer side and a backside layer having a Young's modulus smaller than that of the metal layer and provided on the opposite side of the metal layer from the active material layer.

[0015] According to the all-solid-state secondary battery described in (1) above, it is possible to provide an all-solid-state secondary battery in which short circuits are suppressed while having an active material layer containing a metal or an alloy thereof capable of absorbing or releasing alkali metal ions.

[0016] (2) In the all-solid-state secondary battery described in (1) above, the current collector may include the metal layer on both sides of the back layer.

[0017] In the all-solid-state secondary battery described in (2) above, active material layers can be formed on both sides of the current collector, and therefore the energy density can be increased.

[0018] (3) In the all-solid-state secondary battery according to (1) or (2) above, the current collector may have a tab portion in which the metal layer protrudes in a planar direction from the back surface layer.

[0019] The all-solid-state secondary battery described in (3) above can be easily assembled because the tab lead can be attached to the current collector by welding.

[0020] (4) In the all-solid-state secondary battery according to any one of (1) to (3) above, the back layer may be a resin film or a thermoplastic resin having adhesive properties on both sides.

[0021] In the all-solid-state secondary battery described in (4) above, when a plurality of electrode bodies are stacked to assemble the all-solid-state secondary battery, the electrode bodies can be joined together via the back layer by a low-pressure press, so that the occurrence of cracks in the electrodes during assembly is suppressed.

[0022] The configuration of an all-solid-state secondary battery according to one embodiment of the present invention, the configuration of a power storage device, and a method for manufacturing an all-solid-state secondary battery, as well as other embodiments, will be described in detail. Note that the names of the components (each component) used in each embodiment may differ from the names of the components (each component) used in the background art.

[0023] <<Structure of all-solid-state secondary battery>> An all-solid-state secondary battery according to one embodiment of the present invention (hereinafter, also simply referred to as "all-solid-state secondary battery") includes an electrode body in which a pair of electrodes, i.e., a positive electrode and a negative electrode, are arranged opposite each other with a solid electrolyte layer interposed therebetween, and a container that accommodates the electrode body. The electrode body is usually of a laminate type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a solid electrolyte layer interposed therebetween. The electrode body may also be of a so-called "bipolar type" in which a positive electrode active material layer is formed on one surface of a conductive base material, and a negative electrode active material layer is formed on the other surface.

[0024] FIG. 1 shows an example of an all-solid-state secondary battery. The all-solid-state secondary battery 10 is a secondary battery in which a positive electrode 1 and a negative electrode 2 are arranged with a solid electrolyte layer 3 interposed therebetween. The positive electrode 1 has a positive electrode current collector 4 and a positive electrode active material layer 5. The negative electrode 2 has a negative electrode current collector 7 and a negative electrode active material layer 6. In the all-solid-state secondary battery 10 shown in FIG. 1, the negative electrode active material layer 6, the solid electrolyte layer 3, the positive electrode active material layer 5, and the positive electrode current collector 4 are laminated in this order on the negative electrode current collector 7. In addition, in the all-solid-state secondary battery 10 shown in FIG. 1, the positive electrode current collector 4 includes a metal layer 4a provided on the positive electrode active material layer 5 side, and a back layer 4b having a smaller Young's modulus than the metal layer 4a, which is provided on the opposite side of the positive electrode active material layer 5 with respect to the metal layer 4a. Note that the all-solid-state secondary battery may include the negative electrode current collector 7 including a metal layer and a back layer.

[0025] <Electrode> The electrode has a current collector and an active material layer disposed on the current collector directly or via an intermediate layer.

[0026] (current collector) A positive electrode current collector 4 and a negative electrode current collector 7 are used as the current collectors, and at least one of them includes a metal layer and a back layer having a smaller Young's modulus than the metal layer.

[0027] When the current collector includes a back layer, the portion other than the back layer, and when the current collector does not include a back layer, the current collector itself (hereinafter, collectively referred to as the "conductive part of the current collector") each have electrical conductivity. Whether or not the current collector has electrical conductivity is determined by whether or not the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 The threshold value is Ω·cm.

[0028] When the electrode is a positive electrode 1, the material of the collector conductive part is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. Examples of the collector conductive part include foil, vapor deposition film, mesh, and porous material, and foil is preferred from the viewpoint of cost. Therefore, the collector conductive part of the positive electrode 1 is preferably an aluminum foil or an aluminum alloy foil. Examples of aluminum or an aluminum alloy include A1085, A3003, and A1N30, which are specified in JIS-H-4000 (2014) or JIS-H-4160 (2006). The collector conductive part of the positive electrode 1 may be one in which another material having conductivity is arranged on the surface of the above material.

[0029] The average thickness of the positive electrode current collector 4 is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode current collector 4 within the above range, it is possible to increase the strength of the positive electrode current collector 4 and to increase the energy density per volume of the all-solid-state secondary battery.

[0030] When the electrode is a negative electrode 2, the material of the collector conductive part is a metal such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or an alloy thereof, or a carbonaceous material. Among these, copper or a copper alloy is preferred. In addition, when the negative electrode 2 includes a metal layer and a back layer, it goes without saying that the material of the metal layer does not include a material consisting only of a carbonaceous material. Examples of the collector conductive part include foil, vapor deposition film, mesh, and porous material, and foil is preferred from the viewpoint of cost. Therefore, the negative electrode collector conductive part is preferably copper foil or copper alloy foil. Examples of copper foil include rolled copper foil and electrolytic copper foil. The collector conductive part of the negative electrode 2 may be one in which another material having conductivity is arranged on the surface of the above material.

[0031] The average thickness of the negative electrode current collector 7 is preferably from 2 μm to 35 μm, more preferably from 3 μm to 30 μm, further preferably from 4 μm to 25 μm, and particularly preferably from 5 μm to 20 μm. By setting the average thickness of the negative electrode current collector 7 within the above range, it is possible to increase the strength of the negative electrode current collector 7 and to increase the energy density per volume of the all-solid-state secondary battery.

[0032] When the negative electrode active material layer 6 described later has electrical conductivity, it is not necessary to use the negative electrode current collector 7. In this case, the positive electrode current collector 4 includes the metal layer 4a and the back layer 4b.

[0033] The back layer included in the current collector together with the metal layer has a smaller Young's modulus than the metal layer. By including the back layer in at least one of the positive electrode current collector 4 and the negative electrode current collector 7, even if the active material layer described later includes a metal or its alloy capable of occluding or releasing alkali metal ions, it is possible to suppress short circuit during charging and discharging. This is presumed to be due to the following mechanism of action. The active material layer including a metal or its alloy capable of occluding or releasing alkali metal ions expands in volume by occluding alkali metal ions during charging or discharging, and a compressive load is applied to the electrode. Due to this compressive load, the electrode is deformed not only in the compression direction, i.e., in the direction in which the thickness decreases, but also in the direction in which the area expands. The current collector in the electrode is unable to follow the deformation in the direction in which the area expands, and breaks, causing a short circuit in the all-solid-state secondary battery of the conventional structure. However, when the current collector includes, together with the metal layer, a back layer having a smaller Young's modulus than the metal layer, the back layer, which is more easily deformed, deforms in the direction of area expansion without fracturing before the metal layer, and suppresses deformation in the direction of area expansion of the metal layer, thereby suppressing fracture of the current collector and, as a result, suppressing short-circuiting of the all-solid-state secondary battery.

[0034] Here, the Young's modulus of the metal layer and the back layer is based on the value listed in the "Chemical Handbook" published by Maruzen Publishing. The materials of the metal layer and the back layer are identified in order to match the material names listed in the handbook. The material of the metal layer can be identified by removing the active material layer with ethanol or the like, exposing the metal layer, and performing a qualitative analysis using energy dispersive spectroscopy (EDS). The material of the back layer can be identified by exposing the back layer and performing a qualitative analysis using infrared absorption spectroscopy (IR), pyrolysis gas chromatography mass spectrometry (PGS-MS), or the like. The back layer can be exposed by dissolving the metal layer with a soluble acid, peeling off the metal layer, and removing it. If the back layer can be directly subjected to measurement and it is expected that the Young's modulus of the back layer can be obtained more accurately by doing so, it is measured in accordance with JIS-K-7127 (1999) "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets".

[0035] The material of the back layer is not particularly limited as long as it has a smaller Young's modulus than the metal layer. Examples of the material of such a back layer include polymeric materials such as resin and rubber. Among these, polyimide, polyethylene terephthalate (PET), polytetrafluoroethylene, etc. are preferred in terms of ease of availability and processing.

[0036] The back layer is preferably a resin film or a thermoplastic resin having adhesive properties on both sides. By forming the back layer from a resin film or a thermoplastic resin having adhesive properties on both sides, when a plurality of electrode bodies are stacked to assemble an all-solid-state secondary battery, the electrodes can be joined together via the back layer by a low-pressure press, so that the occurrence of cracks in the electrodes due to pressure during assembly can be suppressed. Examples of adhesive resins or thermoplastic resins constituting such a back layer include acrylic resins, rubber resins, silicone resins, and urethane resins.

[0037] The current collector including the metal layer and the back layer may have a metal layer on both sides of the back layer. A current collector having such a structure can have an active material layer formed on both sides thereof, as in the case of a conventional current collector.

[0038] The current collector preferably has a tab portion in which the metal layer protrudes in a planar direction from the back layer. A current collector having such a structure has the advantage that a tab lead can be attached to the tab portion by welding, making it easier to assemble an all-solid-state secondary battery. In particular, when the current collector has metal layers on both sides of the back layer, the metal layer of the current collector has a tab portion protruding in a planar direction from the back layer, which reduces the risk that the presence of the back layer will make it difficult to attach the tab lead to the tab portion by welding.

[0039] (Middle class) The intermediate layer is a layer disposed between the current collector and the active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the current collector and the active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0040] (active material layer) The active material layer includes an electrode active material. Here, the electrode active material in the present disclosure means a material that is electrochemically oxidized and reduced in the all-solid-state secondary battery. Therefore, the above-mentioned collector conductive portion does not correspond to the electrode active material. The electrode active material is either a positive electrode active material or a negative electrode active material. When the electrode active material includes a positive electrode active material, the active material layer becomes a positive electrode active material layer 5, and the electrode becomes a positive electrode 1. On the other hand, when the electrode active material includes a negative electrode active material, the active material layer becomes a negative electrode active material layer 6, and the electrode becomes a negative electrode 2. At least one of the positive electrode active material layer 5 and the negative electrode active material layer 6 includes, as the electrode active material, a metal or an alloy thereof that can occlude or release an alkali metal ion. The active material layer includes optional components such as a conductive agent, a binder (binding agent), a thickener, a filler, and a solid electrolyte, as necessary.

[0041] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion all-solid-state secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 crystal structure, lithium transition metal composite oxides having a spinel crystal structure, polyanion compounds, chalcogen compounds, and sulfur. In addition, the positive electrode active material may be a material listed as a negative electrode active material (excluding metal Li) described later. Examples of the lithium transition metal composite oxides having an α-NaFeO2 crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β)]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ) O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer 5, one of these materials may be used alone, or two or more of them may be mixed and used.

[0042] The positive electrode active material may be particles (powder) or a film. When the positive electrode active material is particles, the average particle size is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer 5 is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0043] The positive electrode active material may have another substance having ion conductivity on its surface. Examples of the other substance having ion conductivity include LiNbO3, Li2TiO3, Li2Ti2O5, and Li4Ti5O12 , Li2ZrO3, LiTaO3, etc. The form of the other substance having ion conductivity on the surface of the positive electrode active material is not limited, and may be, for example, a film-like coating or particles attached thereto.

[0044] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.

[0045] The content of the positive electrode active material in the positive electrode active material layer 5 is preferably 20% by mass to 90% by mass, more preferably 30% by mass to 85% by mass, and even more preferably 40% by mass to 80% by mass. By setting the content of the positive electrode active material within the above range, it is possible to achieve both a high energy density and a low resistance of the positive electrode active material layer 5.

[0046] The negative electrode active material can be appropriately selected from known negative electrode active materials. As the negative electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used.

[0047] When the negative electrode active material layer 6 contains a metal or an alloy thereof capable of absorbing or releasing an alkali metal ion, examples of the negative electrode active material to be used include metals or semimetals such as metal Li, Si, Sn, Ag, Zn, Ca, Al, Mg, and In, or alloys thereof. In addition, when the alkali metal ion is Li ion, metal Li is strictly a substance that dissolves or precipitates Li, but in the present disclosure, this dissolution or precipitation is also treated as absorption or release in a broad sense. Examples of metal alloys capable of absorbing or releasing an alkali metal ion include Li-Ag alloy, Li-Zn alloy, Li-Ca alloy, Li-Al alloy, Li-Mg alloy, Li-In alloy, Li-Si alloy, Li-Sn alloy, Li-Au alloy, Sn-Cu alloy, and Sn-Co alloy.

[0048] When the positive electrode active material layer 5 contains a metal or an alloy thereof capable of absorbing or releasing alkali metal ions as a positive electrode active material, the negative electrode active material is a metal oxide or semi-metal oxide such as Si oxide, Ti oxide, or Sn oxide; Li4Ti5O 12 , LiTiO 2、 The material may be any one of titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, graphite, non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon), etc. In the negative electrode active material layer 6, one of these materials may be used alone, or two or more of them may be used in combination.

[0049] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0050] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0051] Here, the "discharged state" refers to a state in which the negative electrode active material carbon material is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released. For example, in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, the state is one in which the open circuit voltage is 0.7 V or more.

[0052] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0053] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0054] The negative electrode active material may be particles (powder) or a film. When the negative electrode active material is particles, the average particle size may be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the production or handling of the negative electrode active material becomes easy. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverizing method and the classifying method can be selected, for example, from the methods exemplified in the above positive electrode 1.

[0055] When a particulate negative electrode active material is used in the negative electrode active material layer 6, the content of the negative electrode active material is preferably 20% by mass or more and 80% by mass or less, and more preferably 30% by mass or more and 70% by mass or less. By setting the content of the negative electrode active material within the above range, it is possible to achieve both a high energy density and manufacturability of the negative electrode active material layer 6.

[0056] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Note that when the active material is a carbon material such as graphite or non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon), these are not included in the conductive agent. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a composite material of carbon black and CNT may be used. Among these, fibrous carbonaceous materials are preferred, and CNTs are particularly preferred.

[0057] The content of the conductive agent in the active material layer is preferably 1 mass % or more and 25 mass % or less, and more preferably 3 mass % or more and 15 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the all-solid-state secondary battery can be increased.

[0058] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0059] The content of the binder in the active material layer is preferably from 0.1% by mass to 10% by mass, and more preferably from 0.5% by mass to 9% by mass. By setting the content of the binder in the above range, the active material can be stably held.

[0060] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like.

[0061] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.

[0062] The solid electrolyte can be appropriately selected from known solid electrolytes. For example, sulfide solid electrolytes, halide solid electrolytes, oxide solid electrolytes, etc. can be used as the solid electrolyte. Among these, sulfide solid electrolytes are preferred because they are easily in contact with the active material by plastic deformation. Sulfide solid electrolytes include Li6PS5Cl, Li2S-P2S5, LiI-Li2S-P2S5, and Li 10 Ge-P2S 12, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Li3N, Li2S-SiS2, Li2S-S iS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S 2n (where m and n are positive numbers, and Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is any of P, Si, Ge, B, Al, Ga, and In.) The halide solid electrolyte is generally represented by the formula Li x M y Compounds represented by X6 are preferred, and examples thereof include Li3YCl6, Li3YBr6, Li3YI6, Li3InCl6, Li3InBr6, Li3InF6, Li2ZrCl6, Li3ErCl6, Li3ErBr6, Li3DyCl6, Li3DyBr6, Li3GdCl6, Li3GdBr6, Li3HoCl6, Li3HoBr6, Li3LaCl6, Li3LaBr6, Li3NdCl6, Li3NdBr6, Li3ScCl6, Li3ScBr6, Li3ScF6, Li3SmCl6, Li3SmBr6, Li3TbCl6, Li3TbBr6, Li3TmCl6, Li3TmBr6, Li3AlF6, Li3TiF6, Li3GaF6, and Li3GeF6. The oxide solid electrolyte is Li7La3Zr2O 12 , Li 0.5 La 0.5 Examples include TiO3, LiTi2(PO4)3, Li3BO3-Li2CO3, Li3BO3-Li2SO4, etc.

[0063] The content of the solid electrolyte in the active material layer is preferably from 5% by mass to 60% by mass, and more preferably from 15% by mass to 50% by mass.

[0064] When the active material layer is a positive electrode active material layer 5, it may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, I, etc., typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, etc., and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, W, etc., as components other than the positive electrode active material, conductive agent, binder, thickener, filler, and solid electrolyte.

[0065] When the active material layer is a negative electrode active material layer 6, it may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, I, etc., typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, etc., and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, W, etc., as components other than the negative electrode active material, conductive agent, binder, thickener, filler, and solid electrolyte.

[0066] A preferred combination of electrodes is a combination of a negative electrode 2 having a negative electrode active material layer 6 containing a metal or an alloy thereof capable of occluding or releasing alkali metal ions, and a positive electrode 1 having a positive electrode current collector 4 including a metal layer 4a and a back layer 4b. With this combination, the effect of the back layer 4b in suppressing deformation in the direction in which the area of ​​the metal layer 4a increases becomes significant, and breakage of the current collector and the resulting short circuit of the all-solid-state secondary battery are effectively suppressed.

[0067] <Solid electrolyte layer> The solid electrolyte layer 3 includes a solid electrolyte. As the solid electrolyte, the above-mentioned solid electrolytes that can be used for electrodes can be used.

[0068] <<Configuration of the power storage device>> The all-solid-state secondary battery of this embodiment can be mounted as a power storage unit (battery module) formed by assembling a plurality of all-solid-state secondary batteries in a power source for an automobile such as an electric vehicle (EV), a hybrid vehicle (HEV), or a plug-in hybrid vehicle (PHEV), a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technology of the present invention may be applied to at least one all-solid-state secondary battery included in the power storage unit. 2 shows an example of a power storage device 30 in which power storage units 20, each of which is an assembly of two or more electrically connected all-solid-state secondary batteries 10, are further assembled. The power storage device 30 may include a bus bar (not shown) that electrically connects the two or more all-solid-state secondary batteries 10, a bus bar (not shown) that electrically connects the two or more power storage units 20, and the like. The power storage unit 20 or the power storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more all-solid-state secondary batteries 10.

[0069] <<Manufacturing method for all-solid-state secondary batteries>> A method for producing an all-solid-state secondary battery according to one embodiment of the present invention includes, for example, forming a positive electrode active material layer 5 on a positive electrode current collector 4, forming a negative electrode active material layer 6 on a negative electrode current collector 7, forming a solid electrolyte layer 3, and laminating the positive electrode 1 and negative electrode 2 with the solid electrolyte layer 3 interposed therebetween to form an electrode body. The electrode body can also be produced by stacking the positive electrode current collector 4, the positive electrode active material layer 5, the solid electrolyte layer 3, the negative electrode active material layer 6, and the negative electrode current collector 7 in this order and compression-molding them simultaneously.

[0070] <Other embodiments> The all-solid-state secondary battery of the present invention is not limited to the above-mentioned embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment can be added to the configuration of another embodiment, and a part of the configuration of one embodiment can be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment can be deleted. Also, a well-known technique can be added to the configuration of one embodiment. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0072] [Example 1] (Formation of Positive Electrode Active Material Layer) The positive electrode active material is a lithium-ion battery with the composition LiNi, whose surface is coated with LiNbO3. 0.6 Co 0.2 Mn 0.2 A powder (average particle size 3 μm) composed of lithium transition metal composite oxide particles represented by O2 (NCM622) was prepared. A sulfide solid electrolyte (average particle size 0.6 μm) represented by the composition formula Li6PS5Cl was prepared as a solid electrolyte. Vapor grown carbon fiber (VGCF (registered trademark), average diameter 150 nm, manufactured by Showa Denko K.K.) was prepared as a conductive agent. Styrene butadiene rubber (SBR) was prepared as a binder. In a glove box with an argon atmosphere, the positive electrode active material, the solid electrolyte, and the conductive agent were mixed using a hybrid mixer. Next, the binder and butyl butyrate as a solvent were added to this mixture, and the mixture was kneaded with the hybrid mixer to prepare a paste for forming a positive electrode active material layer. The mass ratio of solids in the paste for forming a positive electrode active material layer was (positive electrode active material):(solid electrolyte):(conductive agent):(binder)=76:20:2:2. For the metal layer for the positive electrode current collector, a 20 μm thick Al foil (Young's modulus of Al: 70 GPa) was cut into a 30 mm × 30 mm square shape, and a 30 mm × 30 mm square slightly adhesive PET film (manufactured by Nippa Corporation) with a 20 mm × 20 mm opening in the center was attached to one side. The above paste for forming the positive electrode active material layer was applied to the film using a multi-applicator (MA100 manufactured by Cortec Corporation) to a basis weight of 45 mg cm (solid content). -2The surface of the Al foil on which the weakly adhesive PET film was attached was coated so that the weakly adhesive PET film was peeled off. In this way, a positive electrode active material layer was formed on one side of the positive electrode current collector metal layer. The positive electrode active material layer was located in the center of the positive electrode current collector metal layer and had a square shape of 20 mm x 20 mm.

[0073] (Formation of solid electrolyte layer) As the solid electrolyte and the binder, the same type of sulfide solid electrolyte and styrene-butadiene rubber as those used in forming the positive electrode active material layer were prepared. In a glove box with an argon atmosphere, a binder and decane as a solvent were added to the solid electrolyte, and the mixture was kneaded with a hybrid mixer to prepare a paste for forming a solid electrolyte layer. The mass ratio of the solid content in the paste for forming a solid electrolyte layer was (solid electrolyte):(binder)=95:5. The paste for forming the solid electrolyte layer was applied to the surface of the metal layer for the positive electrode current collector on which the positive electrode active material layer was formed, using a multi-applicator (MA100, manufactured by COATEC Co., Ltd.) with a basis weight of 15 mg cm (solid content). -2 More than 25mg cm -2 The coating was performed as follows: This was dried in a dryer in an argon atmosphere set at a temperature at which the organic solvent volatilized, to form a solid electrolyte layer on the surface of the positive electrode current collector metal layer on the side on which the positive electrode active material layer was formed. A 60 μm thick polyimide tape (Young's modulus of polyimide: 3.0 GPa) having adhesive on one side was attached as a back layer to the entire surface of the metal layer for positive electrode collector opposite the surface on which the positive electrode active material layer was formed. Two sets of these were prepared and stacked so that the polyimide tapes were in contact with each other to form a laminate of the positive electrode / solid electrolyte layer.

[0074] (Preparation of negative electrode) An intermediate layer was placed on one side of a 20 μm-thick Cu foil to prepare a negative electrode current collector. Powder (average particle size 0.8 μm) composed of metal Si particles was prepared as the negative electrode active material. As the solid electrolyte, conductive agent, and binder, the same type of sulfide solid electrolyte, vapor-grown carbon fiber, and styrene-butadiene rubber as those used in forming the positive electrode active material layer were prepared, respectively. In a glove box with an argon atmosphere, the negative electrode active material, the solid electrolyte, and the conductive agent were mixed using a hybrid mixer. Next, the binder and butyl butyrate as a solvent were added to this mixture, and the mixture was kneaded with the hybrid mixer to prepare a paste for forming a negative electrode active material layer. The mass ratio of solids in the paste for forming a negative electrode active material layer was (negative electrode active material):(solid electrolyte):(conductive agent):(binder)=44:50:3:3. The paste for forming the negative electrode active material layer was applied to the surface of the negative electrode current collector on which the intermediate layer was disposed, using a multi-applicator (MA100, manufactured by Cortec Co., Ltd.) to a solid content of 45 mg cm -2 The coated layer was dried in a dryer in an argon atmosphere set at a temperature at which the organic solvent volatilized, forming a layer of the negative electrode active material on one side of the negative electrode current collector. This was punched out into a square shape of 20 mm x 20 mm to form a negative electrode.

[0075] (Preparation of electrode body) In a glove box in an argon atmosphere, the negative electrodes were placed on the solid electrolyte layers formed so as to cover the two positive electrode active material layers, respectively, to obtain a laminate. As shown in FIG. 3, this laminate is formed by laminating a negative electrode current collector 7, a negative electrode active material layer 6, a solid electrolyte layer 3, a positive electrode active material layer 5, a positive electrode current collector 4 (4a, 4b, 4a), a positive electrode active material layer 5, a solid electrolyte layer 3, a negative electrode active material layer 6, and a negative electrode current collector 7 in this order. The obtained laminate was sealed in a flexible sealing material under reduced pressure, and then removed from the glove box, and warm isostatic pressing was performed under conditions of 160°C and 1000 MPa to bond each layer to obtain an electrode body.

[0076] (Production of all-solid-state secondary batteries) In a glove box under an argon atmosphere, the sealant was opened, the electrode body was taken out, and the electrode body was sealed in an exterior body to obtain the all-solid-state secondary battery according to Example 1.

[0077] [Comparative Example 1] Except for changing the procedure for preparing the positive electrode to the following, an all-solid-state secondary battery according to Comparative Example 1 was obtained in the same procedure as in Example 1. As a positive electrode current collector, an Al foil having a thickness of 20 μm was prepared, and a paste for forming a positive electrode active material layer was applied to both sides of the positive electrode current collector and dried to form a positive electrode active material layer. The positive electrode active material layer was located in the center of a square positive electrode current collector having a size of 30 mm×30 mm on each side, and had a square shape of 20 mm×20 mm. Next, a rectangular metal tab having a size of 10 mm×8 mm was attached to a part of the positive electrode current collector exposed with a width of 5 mm on each of the four sides corresponding to the peripheral parts of both sides, and a fluororesin tape having a thickness of 130 μm (manufactured by Nitto Denko Corporation, Nitoflon tape) was attached to cover all of the exposed Al foil to form a positive electrode.

[0078] [Comparative Example 2] An all-solid-state secondary battery according to Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the manufacturing procedures for the positive electrode and the electrode body were changed as follows. A square-shaped positive electrode active material layer of 20 mm x 20 mm was formed on the center of each surface of a square-shaped positive electrode collector of 30 mm x 30 mm, and a square-shaped solid electrolyte layer of 20 mm x 20 mm was formed on both sides of the positive electrode so as to cover the positive electrode active material layer. After attaching a polyimide tape of 60 μm in thickness to the positive electrode collector exposed around the solid electrolyte layer, a negative electrode was placed on the solid electrolyte layer and hot isostatic pressing was performed to bond each layer to obtain an electrode body.

[0079] <Evaluation> A charge / discharge test was carried out on each of the obtained all-solid-state secondary batteries at 50° C. in the following manner. A constant current / constant voltage charge was performed with a charge current of 0.1 C and a charge cut-off voltage of 4.25 V. The charge was terminated when the charge current reached 0.025 C. A rest period of 10 minutes was then provided. A constant current discharge was then performed with a discharge current of 0.1 C and a discharge cut-off voltage of 2.5 V.

[0080] As a result of the charge / discharge test, each of the all-solid-state secondary batteries according to the comparative examples experienced a short circuit during charging and was unable to be charged or discharged thereafter, whereas each of the all-solid-state secondary batteries according to the examples was able to be charged and discharged without experiencing a short circuit.

[0081] [Example 2] An all-solid-state secondary battery according to Example 2 was obtained in the same manner as in Example 1, except that the procedure for preparing the positive electrode was changed as follows. As the metal layer for the positive electrode collector, an Al foil having a thickness of 20 μm was cut into a shape in which a tab portion having a width of 8 mm extended 10 mm from one side of a square shape of 30 mm×30 mm, and a paste for forming a positive electrode active material layer was applied only to one side of the metal layer for the positive electrode collector, and dried to form a positive electrode active material layer. The positive electrode active material layer was located in the center of the square-shaped portion of the metal layer for the positive electrode collector, and had a square shape of 20 mm×20 mm. Two sheets of this were prepared. On only one of these sheets, a PET film (Young's modulus of PET: 2.0 GPa) having a thickness of 10 μm, which is a resin film having adhesive properties on both sides, was cut into a square shape of 30 mm×30 mm and attached as a back layer to the square-shaped portion on the surface opposite to the surface on which the positive electrode active material layer was formed of the metal layer for the positive electrode collector. The surface of the remaining positive electrode current collector metal layer opposite to the surface on which the positive electrode active material layer was formed was attached to the back layer to form a positive electrode. In this way, a laminated electrode body as shown in Fig. 4 was obtained. In the obtained laminated electrode body, the rectangular tab portion of the metal layer 4a of the positive electrode current collector 4, measuring 8 mm x 10 mm, was not opposed to any of the solid electrolyte layer 3, the negative electrode active material layer 6, or the back layer 4b.

[0082] In the all-solid-state secondary battery according to Example 2, since the back layer 4b is a resin film having adhesive properties on both sides, it was possible to join a plurality of electrode bodies together by a low-pressure press. In addition, since the positive electrode current collector 4 has a tab portion, it was possible to attach a tab lead by resistance welding. In this way, the all-solid-state secondary battery according to Example 2 was easily assembled.

[0083] <Evaluation> A charge / discharge test was carried out on the all-solid-state secondary battery according to Example 2 in the same manner as in Example 1 and Comparative Examples 1 and 2. As a result, it was possible to charge and discharge the battery without causing a short circuit. [Industrial Applicability]

[0084] An all-solid-state secondary battery according to one aspect of the present invention is useful in that it has an active material layer containing a metal or an alloy thereof capable of occluding or releasing alkali metal ions, while suppressing short circuits during charging and discharging. [Explanation of symbols]

[0085] 1 positive electrode 2 negative electrode 3 Solid electrolyte layer 4 Positive electrode current collector 4a (Positive electrode current collector) metal layer 4b Back layer (of positive electrode current collector) 5 Cathode active material layer 6 Negative electrode active material layer 7 Negative electrode current collector 10 All-solid-state secondary battery 20 Energy Storage Unit 30 Energy storage device

Claims

1. A pair of electrodes faces each other via a solid electrolyte layer, At least one of the pair of electrodes has an active material layer containing a metal or an alloy thereof capable of absorbing or releasing alkali metal ions, At least one of the pair of electrodes has a current collector including a metal layer provided on the active material layer side, and a back layer provided on the opposite side of the metal layer from the active material layer and having a Young's modulus smaller than that of the metal layer. All-solid-state secondary battery.

2. The all-solid-state secondary battery according to claim 1 , wherein the current collector includes the metal layer on both sides of the back surface layer.

3. The all-solid-state secondary battery according to claim 1 , wherein the current collector has a tab portion in which the metal layer protrudes in a planar direction from the back surface layer.

4. The all-solid-state secondary battery according to claim 1 , wherein the back layer is a resin film or a thermoplastic resin having adhesive properties on both sides.

Citation Information

Patent Citations

  • All-solid secondary battery, lamination all-solid secondary battery and manufacturing method of all-solid secondary battery

    JP2019121558A

  • All-solid battery and manufacturing method thereof

    JP2020021551A

  • All solid-state battery laminate

    JP2020136261A

  • All-solid battery and all-solid battery system

    JP2021002495A

  • Current collector for all-solid-state battery and all-solid-state battery

    JP2021099934A